Internationalization of higher education institutions: the case study of the Polytechnic Institute of Bragança - Veloso, Cláudia M. (2020)
Higher Education Institutions (HEI) operate in a competitive environment that forces them to adopt a new strategic position seeking to position themselves better in a greatly competitive, dynamic and differentiated market. Internationalisation is becoming one of the main key factor and strategic priorities of HEI all world. Most HEI include internationalisation, as a part of their competitive strategies once is a way to promote cooperation and mobility for both students and staff and knowledge transfer between institutions. The aim of the research is to analyse and evaluate the international academic mobility in the Polytechnic Institute of Bragança (IPB, Portugal). The aim is to contribute to the gradual interest of the understanding of the phenomenon of academic mobility and its impacts on IPB, once foreign students are an asset to HEI, during the stay where they are studying, and as well the staff mobility. In addition, given the relevance and importance of the internationalisation strategy followed by the IPB and its international both students and staff mobility, it is intended that the results of this will help the decision makers in the IPB to develop better strategies that will support the internationalisation process within IPB.